Very low birth weight piglets show improved cognitive performance in the spatial cognitive holeboard task - Antonides, Alexandra; Schoonderwoerd, Anne C.; Nordquist, Rebecca E.; van der Staay, Franz Josef (Frontiers in Behavioral Neuroscience, 2015)
Low birth weight (LBW) is common in humans and has been found to cause lasting cognitive and developmental deficits later in life. It is thought that the primary cause is intra-uterine growth restriction due to a shortage of oxygen and nutrients supply to the fetus. Pigs appear to be a good model animal to investigate long-term cognitive effects of LBW, as LBW is common in commercially farmed breeds of pigs. Moreover, pigs are developmentally similar to humans and can be trained to perform complex tasks. In this study, we trained ten very low birth weight (vLBW) piglets and their ten normal birth weight (NBW) siblings in a spatial cognitive holeboard task in order to investigate long-term cognitive effects of LBW. In this task, four out of sixteen holes contain a hidden food reward, which allows measuring working memory (short-term) and reference memory (long-term) in parallel. Piglets were trained for 46-54 trials during the acquisition phase, followed by a 20-trial reversal phase in which a different set of four holes was baited. Both groups acquired the task and improved their performance over time. A mixed model repeated measures ANOVA revealed that vLBW piglets showed a better reference memory performance than NBW piglets in both the acquisition and reversal phase. Additionally, the vLBW piglets fell back less in working memory scores than the NBW animals when switched to the reversal phase. These findings are contrary to findings in humans. Moreover, vLBW pigs had lower hair cortisol concentrations than NBW pigs in flank hair at 12 weeks of age. These results could indicate that restricted intra-uterine growth causes compensatory mechanisms to arise in early development that result in beneficial effects for vLBW piglets, increasing their low survival chances in early-life competition.